ChemInform Abstract: A New Dimeric Naphtho‐γ‐pyrone from an Endophytic Fungus Aspergillus niger AKRN Associated with the Roots of Entandrophragma congoense Collected in Cameroon. Issue 4 (January 2016) - Happi, Gervais M.; Kouam, Simeon Fogue; Talontsi, Ferdinand M.; Nkenfou, Celine N.; Longo, Frida; Zuehlke, Sebastian; Douanla‐Meli, Clovis; Spiteller, Michael
Abstract: isolation and structure elucidation of 2‐hydroxydihydronigerone (I)